1975
DOI: 10.1901/jaba.1975.8-247
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Specific Erotic Cues in Sexual Deviations by Audiotaped Descriptions1

Abstract: Using audiotaped descriptions of sexual experiences and a direct measure of penile erection, it is possible to specify more precisely erotic cues in sexual deviates. Results indicated that such cues are highly idiosyncratic. Some tentative conclusions and suggested application for the method are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Proponents have argued that plethysmography can identify rapists and can differentiate those with the most victims and those who show sadistic behavior (15)(16)(17)(18)(19)(20)(21)(22). Plethysmography has been successful in identifying child molesters, and in differentiating offenders who use excessive force in their assaults (23-25).…”
Section: Assessmentmentioning
confidence: 99%
“…Proponents have argued that plethysmography can identify rapists and can differentiate those with the most victims and those who show sadistic behavior (15)(16)(17)(18)(19)(20)(21)(22). Plethysmography has been successful in identifying child molesters, and in differentiating offenders who use excessive force in their assaults (23-25).…”
Section: Assessmentmentioning
confidence: 99%
“…We suspect that the major problem with evaluating rapists' physiologic responses has been that researchers have presented stimuli of a sexual nature (Karacan et al, 1974;Kercher and Walker, 1973), but have failed to present rapists with explicit sexual stimuli depicting the act of rape. Our own assessment involves the presentation of rape and nonrape sexual stimuli and has appeared to differentiate rapists from nonrapists (Abel et al, 1977;Abel et al, 1975;Abel et al, 1974). The three categories of stimuli we have used include scenes of rape, mutually consenting sexual interactions, and violent physical, nonsexual assaults.…”
Section: Factors To Consider During the Physiologic Assessment Of Malmentioning
confidence: 99%
“…In a laboratory study of male 326 R.V. Haning et al subjects monitored with penile strain gauges, both Abel, Blanchard, Barlow and Mavissakalian, (1975) and Abrahamson, Barlow, Beck, Sakheim and Kelly (1985) showed that the subjects' erectile responses to audiotapes were augmented when the audiotaped ''partner'' was responding in comparison to when the audio-taped partner was not responding or when the partner's response was ambiguous. Ellis and Symons (1990) found sexually dimorphic content in sexual fantasies (how their imagined partners respond to them) was an important part of women's sexual fantasies but not of men's.…”
Section: Empathy and Autonomic Empathic Responsesmentioning
confidence: 99%
“…First of all, as detailed in the introduction, empathic cardiovascular responses are well documented (Levenson & Ruef, 1992) so there is precedent for autonomic responses being produced empathetically. Second, with regard to empathic turn-on, it is well established that some individuals can produce physiological sexual arousal in response to self-induced sexual fantasy or erotic audiotape (Abel et al, 1975;Abrahamson et al, 1985;Stock & Greer, 1982), that some can reach orgasm through fantasy alone (Kinsey, Pomeroy, & Martin 1948, pp. 517-530;Whipple, Ogden, & Komisaruk, 1992), and that many report reaching orgasm during sleep (83% of males [Kinsey, Pomeroy, & Martin 1948, pp.…”
Section: Mechanism(s) Behind Empathic Sexual Responsesmentioning
confidence: 99%